Indications, Timing and Outcomes of Tracheostomy: A Hospital Based Descriptive Study of Head and Neck Surgery Division Dr. Soetomo Hospital Surabaya - Dwi Agustina, Sisca; Dwi Wibowo, Marjono; Sahudi, Sahudi (Jurnal Health Sains, 2025)
Tracheostomy is a surgical procedure that creates an opening in the anterior tracheal wall, performed either urgently or electively based on the severity of upper airway obstruction and underlying conditions. Over time, the indications and complications of tracheostomy have evolved, necessitating further evaluation of its use in clinical settings. This study aims to analyze the common indications, timing, and outcomes of tracheostomy in patients treated under the Head and Neck Surgery Division of Dr. Soetomo Hospital Surabaya. This retrospective descriptive study included all patients who underwent tracheostomy in the Head and Neck Surgery Division from January 2019 to December 2023. Data were obtained from medical records, processed, and analyzed descriptively using IBM SPSS Statistics. Over a five-year period, a total of 450 patients underwent tracheostomy, with the majority aged 51-60 years, and male patients predominating. The most common indication for tracheostomy was mechanical ventilation, followed by upper airway obstruction (146 cases). The most frequently encountered complication was stomal infection, along with bleeding. The most common diagnosis among tracheostomy patients included prolonged ventilator dependence, maxillofacial trauma, and cervical trauma. Mortality was attributed to underlying diseases rather than tracheostomy-related complications. These findings highlight the continued necessity of tracheostomy in managing upper airway obstruction and prolonged ventilation while emphasizing the importance of infection control measures to minimize complications. Future research should explore long-term functional outcomes, the impact of early versus late tracheostomy, and strategies to reduce postoperative complications. Additionally, studies investigating alternative airway management techniques and their effectiveness compared to traditional tracheostomy could provide valuable insights for optimizing patient care.